2004
DOI: 10.4049/jimmunol.173.12.7239
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 Engagement Acts as a Brake on CD4+ T Cell Proliferation and Cytokine Production but Is Not Required for Tuning T Cell Reactivity in Adaptive Tolerance

Abstract: Adaptive tolerance is the physiologic down-regulation of T cell responsiveness in the face of persistent antigenic stimulation. In this study, we examined the role of CTLA-4 in this process using CTLA-4-deficient and wild-type TCR transgenic, Rag2−/−, CD4+ T cells transferred into a T cell-deficient, Ag-expressing host. Surprisingly, we found that the tuning process of adoptively transferred T cells could be induced and the hyporesponsive state maintained in the absence of CTLA-4. Furthermore, movement to a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 66 publications
(81 reference statements)
1
26
0
1
Order By: Relevance
“…On the one hand, CTLA-4 was critical for the induction of tolerance to tissue Ag and, in these conditions, self-Ag was found to be alone sufficient to initiate pathologic autoimmunity in lymphocyte-depleted recipients reconstituted with self-Ag-specific CTLA-4-deficient CD4 ϩ T cells (40). On the other hand, the same CTLA-4-deficient T cells transferred into systemic Ag-expressing mice became just as hyporesponsive as wild-type cells and adapted their response to the persistent presence of their Ag (41,42). Thus, CTLA-4 does not appear to be as important for T cell adaptation to systemic Ags as it is for tolerance to tissue-restricted Ag.…”
Section: Figurementioning
confidence: 99%
“…On the one hand, CTLA-4 was critical for the induction of tolerance to tissue Ag and, in these conditions, self-Ag was found to be alone sufficient to initiate pathologic autoimmunity in lymphocyte-depleted recipients reconstituted with self-Ag-specific CTLA-4-deficient CD4 ϩ T cells (40). On the other hand, the same CTLA-4-deficient T cells transferred into systemic Ag-expressing mice became just as hyporesponsive as wild-type cells and adapted their response to the persistent presence of their Ag (41,42). Thus, CTLA-4 does not appear to be as important for T cell adaptation to systemic Ags as it is for tolerance to tissue-restricted Ag.…”
Section: Figurementioning
confidence: 99%
“…Expression of another inhibitory receptor, cytotoxic T-lymphocyte antigen 4 (CTLA4), is induced at a high threshold of TCR self reactivity and inhibits T-cell activation by competing with CD28 for ligation with B7 molecules and by transmitting inhibitory signals 48,52,53 . Lack of CTLA4 causes massive accumulation of self-reactive T cells in peripheral lymphoid and nonlymphoid tissues, both by disrupting intrinsic regulation of TCR-induced proliferation 53,54 and by impairing the suppressive function of T R cells. Subtle functional variants of the CTLA4 gene are associated with susceptibility to thyroid autoimmunity and type 1 diabetes in humans and mice 55 .…”
Section: Intrinsic Regulation By Anergy and Biochemical Tuningmentioning
confidence: 99%
“…The T cells that can respond to a single antigen are very limited [2], so rapid proliferation is required to enable a quick immune response. Several reports have indicated that CD4 + T cells could duplicate as quickly as every 5 to 6 h in vivo [3][4][5], which implies a very rapid completion of the cell cycle. The nature of this cycle has yet to be well characterized.…”
Section: Introductionmentioning
confidence: 99%